Designing Elastic Organic Crystals: Highly Flexible Polyhalogenated N‐Benzylideneanilines1. (13th January 2015) - Ghosh, Soumyajit; Mishra, Manish Kumar; Kadambi, Sourabh B.; Ramamurty, Upadrasta; Desiraju, Gautam R.
Abstract The intermolecular interactions and structural features in crystals of seven halogenated N‐benzylideneanilines (Schiff bases), all of which exhibit remarkable flexibility, were examined to identify the common packing features that are the raison d'être for the observed elasticity. The following two features, in part related, were identified as essential to obtain elastic organic crystals: 1) A multitude of weak and dispersive interactions, including halogen bonds, which may act as structural buffers for deformation through easy rupture and reformation during bending; and 2) corrugated packing patterns that would get interlocked and, in the process, prevent long‐range sliding of molecular planes.